Non-concussive head impacts sustained during American football correlate with changes in gut microbiome diversity and composition - Zachary J. Pelland; Aziz Zafar; Ahmet A. Ay; Kenneth Douglas Belanger (PLoS ONE, 2026)
Non-concussive head impacts (NHIs) are a significant health concern among at-risk groups, including athletes and military personnel. NHIs are hits to the head or head acceleration events (HAEs) that do not generate clinically detectable symptoms and are unlikely to meet diagnostic criteria for mild traumatic brain injury (mTBI). The composition of the gut microbiota influences many aspects of health and wellness and can be altered by TBIs and by brain-related diseases and disorders; however, microbiome alterations have not previously been linked to NHIs. We investigated whether NHIs in a cohort of American football players correlate with acute and long-term changes in the gut microbiome. This study monitored head impact exposure, gut microbiome composition, and a breadth of clinical and behavioral factors in a cohort of collegiate American football players across a competition season. Both short- and long-term changes in the microbiome were analyzed for correlation with head impact events and mathematical modeling was used to examine the contribution of NHIs and other clinical factors to these changes. We observe that NHI exposure correlates with changes in microbial diversity and composition three days following a head impact event. Furthermore, the athletes’ gut microbiomes change significantly across the season, with evidence from mixed-effects modeling indicating that the cumulative effects of NHIs contribute to this change. Our results provide strong evidence for a link between NHIs and changes in the diversity and composition of the gut microbiome. The outcomes of this study emphasize the importance of careful monitoring of head impacts, including those that do not generate clinical symptoms.